Clinicopathologic Audit of Salivary Gland Lesions - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Salivary gland lesions present with varied clinical features because of the complex architecture of the glands. A good understanding of the distribution, natural history, epidemiology, and etiopathogenesis is essential for diagnosis and management.Materials and Methods:A retrospective cross-sectional study of all salivary gland lesions seen between January 2007 and December 2016 at the Biopsy Service of Lagos University Teaching Hospital was conducted.Results:There were 224 salivary gland lesions over the 10-year study period; 115 (51.3%) females and 109 (48.7%) males (M/F 1:1.05). The age range was 2 months to 86 years with a mean age of 37.07 years. Salivary gland lesions were more common in the third and fourth decades (18.8% and 18.3%, respectively). There were 55 (24.6%) cystic lesions, 55 (24.6%) benign neoplasms, 84 (37.5%), malignant neoplasms, and 29 (12.9%) inflammatory salivary gland lesions. The ratio of malignant tumors to benign tumors was 1.5:1.Conclusion:Salivary gland lesions are more prevalent in the third and fourth decades of life; malignant tumors were more prevalent than benign tumors. Malignant tumors and inflammatory lesions were more common in males whereas benign and cystic lesions were more common in females.